A construção da identidade no teatro de grupo - Lima, Ábia Matos de (Universidade do Vale do Rio dos Sinos, 2022)
This dissertation aims to analyze the process of building the individual and collective identity of the Grupo de Artes Scenics Adoração em Cena, the group was founded in 2009, with headquarters and headquarters in the Seventh-day Adventist Church, in Taguatinga Centro - DF. The reflection on individual and collective identity is based on cultural-historical theory, with the question: How and in what sense do the social interactions carried out in this artistic laboratory of the Adoração em Cena group affect the personal and collective identity of the individuals participating in it? Gathered in this study, data were collected from a study on individual and collective identity, having the qualitative and quantitative approach as instruments for data collection individual and collective interviews, as well as observation elements focused on the interactions between the participating members in authors, analyzed in the light of contributions from theoretical elaborations, more specifically by Mead (1993), Pardo (1996) and Giddens (2022), among others. The study did not intend to provide new theoretical elements beyond what is already widely contemplated in the consulted bibliography but sought to apply the theoretical learning obtained in the understanding of the identity construction process in question. Despite the limitations of the data actually obtained, it can be concluded that the “group theater” in question has a strong influence on the identity construction process of its participants, which is projected beyond the group.
Keywords: Identidade; Identidade coletiva; Grupo de teatro; Comunicação; Identity; Collective identity; Group theater; Communication; ACCNPQ::Ciências Humanas::Sociologia